Substantia Nigra Echogenicity Signal Correlated with Clinical Features in Patients with Parkinson’s Disease in Xinjiang - Rurui Wei; Yan Zhang; Peishan Li; Zeheng Xu; La Zhang; Yan He; Qinfen Wu; Youcai Shi; Yang Yuan; Abudula Aisha (Parkinson's Disease)
Background. Transcranial sonography (TCS) is a noninvasive test that can reveal structural changes in the substantia nigra (SN) in Parkinson’s disease (PD). The purpose of this study was to investigate the relationship between SN signatures and clinical features in PD patients in a multiethnic region of China. Methods. A total of 147 patients with PD were included in the study, and all of whom had underwent a TCS examination. Clinical information was collected from PD patients, and motor and nonmotor symptoms were assessed using assessment scales. Results. There were differences in the substantia nigra hyperechogenicity (SNH) area between age of onset, visual hallucinations (VH), and UPDRS3.0 II scores (P < 0.05), patients with late onset PD had a greater SNH area than early onset (0.326 ± 0.352 vs. 0.171 ± 0.194), and PD patients presenting with VH had a greater SNH area than those without hallucinations (0.508 ± 0.670 vs. 0.278 ± 0.659), and further multifactorial analysis showed that a high SNH area was an independent risk factor for development of VH. The area under the ROC curve for predicting VH from the SNH area in PD patients was 0.609 (95% CI: 0.444–0.774). There was a positive correlation between the SNH area and UPDRS3.0-II scores, but further multifactorial analysis showed that SNH was not an independent predictor of the UPDRS3.0-II score. Conclusion. A high SNH area is an independent risk factor for development of VH, there is a positive correlation between the SNH area and UPDRS3.0 II score, and TCS has guiding significance in predicting clinical VH symptoms and activities of daily living in PD patients.